Diretrizes de acessibilidade em websites de comércio eletrônico para usuários cegos - Guimarães, Ítalo José Bastos (2021)
The research presents an overview of accessibility on e-commerce websites. The purpose is to analyze existing accessibility guidelines for blind users with a view to their suitability for e-commerce. It is supposed that current accessibility guidelines are not sufficient to address the peculiarities inherent in e-commerce, especially with regard to accessibility barriers imposed on blind users. The methodological approach is based on five steps: (1) study of accessibility guidelines adopted by international and / or national institutions; (2) identification of informational barriers on e-commerce; (3) elaboration of the elements that will guide the guidelines that will be proposed in the thesis; (4) elaboration of an e-commerce Website (prototype) that will be elaborated based on the guidelines proposed in the previous step; and (5) validation of the guidelines suggested in the thesis. The study was carried out with six blind users who evaluated the existing websites, in addition to the prototype developed with the guidelines. In total, 26 accessibility guidelines on e-commerce websites for blind users are presented, separated into three categories, namely: guidelines for the homepage, guidelines related to searching for a product and, finally, guidelines on purchasing procedures. Accessibility guidelines on e-commerce websites presented in the thesis have been validated through testing with blind users. The results showed the efficiency in the proposed guidelines and positive evaluation of all participating users, whose reports proved that the adoption of the proposed guidelines were essential for an intuitive, simple and barrier-free navigation. The data also revealed that no user had difficulty in performing the recognition navigation, search for a product and carrying out the purchase procedures. In addition, a comparative analysis was carried out in relation to the five e-commerce websites analyzed in the study. The prototype with the adoption of accessibility guidelines proved to be more efficient in most of the criteria analyzed, requiring only the adjustment of a guideline that was inserted later. It is also noteworthy that the accessibility guidelines suggested in this study are not intended to remedy all the difficulties encountered by blind users on e-commerce pages or to solve all accessibility problems, but rather represent an alternative contribution to accessibility on Web sites. e-commerce, promoting the inclusion of blind users and providing autonomy so that they can make their purchases with as little difficulty as possible.